Creative Marketing: A Review Article - Saja Hussein Ahmed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Creative marketing represents a contemporary approach in modern marketing characterized by innovation, differentiation, and unconventional strategies in dynamic business environments. Specific Background: The growing complexity of markets and increased customer awareness have positioned creative marketing as a strategic process integrating product, pricing, promotion, and distribution innovations to create value and sustain competitiveness. Knowledge Gap: Despite extensive discussion in the literature, the concept of creative marketing remains ambiguous due to multiple definitions and the lack of a unified conceptual framework. Aims: This article aims to systematically review previous literature, clarify the concept, identify theoretical foundations, and present an integrated framework of creative marketing dimensions and principles. Results: The study reveals that creative marketing encompasses all elements of the marketing mix and relies on organizational culture, cognitive flexibility, and innovative thinking to generate value and support adaptability in complex environments. Novelty: The article provides a structured synthesis that consolidates fragmented perspectives into a comprehensive conceptual understanding of creative marketing. Implications: The findings offer a theoretical reference for researchers and decision-makers to adopt creative marketing strategies, support organizational adaptability, and guide future research development in marketing theory and practice. Highlights:• Integrates Diverse Perspectives Into a Unified Conceptual Structure• Emphasizes Role of Organizational Culture and Flexible Thinking• Identifies Multidimensional Components Across Marketing Activities Keywords: Creative Marketing, Marketing Innovation, Conceptual Framework, Marketing Strategy, Organizational Adaptability.